2021
DOI: 10.1186/s12915-021-01046-9
|View full text |Cite
|
Sign up to set email alerts
|

The Wnt-specific astacin proteinase HAS-7 restricts head organizer formation in Hydra

Abstract: Background The Hydra head organizer acts as a signaling center that initiates and maintains the primary body axis in steady state polyps and during budding or regeneration. Wnt/beta-Catenin signaling functions as a primary cue controlling this process, but how Wnt ligand activity is locally restricted at the protein level is poorly understood. Here we report a proteomic analysis of Hydra head tissue leading to the identification of an astacin family proteinase as a Wnt processing factor. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 21 publications
(24 citation statements)
references
References 76 publications
(172 reference statements)
1
23
0
Order By: Relevance
“…Furthermore, they showed that this negative influence was mutual, given that removal of HyDkk1/2/4-A-expressing gland cells led to ectopic HyWnt3-expressing cell clusters throughout the body column. This inhibitory influence was additionally confirmed by analysis of the impact of Hydra HyDkk1/2/4-A on canonical Wnt signalling in Xenopus [14], and in another recent study showing that knockdown of HyDkk1/2/4-A in combination with ALP treatment led to the formation of ectopic axes in Hydra [40].…”
Section: Submodel For Self-organised Body-axis Formationmentioning
confidence: 53%
See 4 more Smart Citations
“…Furthermore, they showed that this negative influence was mutual, given that removal of HyDkk1/2/4-A-expressing gland cells led to ectopic HyWnt3-expressing cell clusters throughout the body column. This inhibitory influence was additionally confirmed by analysis of the impact of Hydra HyDkk1/2/4-A on canonical Wnt signalling in Xenopus [14], and in another recent study showing that knockdown of HyDkk1/2/4-A in combination with ALP treatment led to the formation of ectopic axes in Hydra [40].…”
Section: Submodel For Self-organised Body-axis Formationmentioning
confidence: 53%
“…However, we want to point out that in late stages of these simulations, Dickkopf patterns re-establish, which might reflect the fact that terminal cell differentiation is not incorporated in our model and ALP-driven effects are only initially given and thus reversible. Finally, we also repeated recent HyDkk1/2/4-A-knockdown experiments [40] with and without ALP treatment (Fig. 4).…”
Section: Resultsmentioning
confidence: 71%
See 3 more Smart Citations